Respuesta :
ok so remember that x^3 times x^3=x^6 so
remember that
a^2+b^2=(a+b)(a-b)
so
(x^2)^2-1^2=(x^2+1)(x^2-1)
x^2-1^2=(x+1)(x-1)
possible factors are (x^2+1), (x^2-1), (x+1), (x-1)
facotred completely so have to chose from (x^2+1), (x+1), (x-1) since the (x^2-1) wasn't factored completely
the only match is C. x-1
remember that
a^2+b^2=(a+b)(a-b)
so
(x^2)^2-1^2=(x^2+1)(x^2-1)
x^2-1^2=(x+1)(x-1)
possible factors are (x^2+1), (x^2-1), (x+1), (x-1)
facotred completely so have to chose from (x^2+1), (x+1), (x-1) since the (x^2-1) wasn't factored completely
the only match is C. x-1